Jul i Islændingesagaerne - Signe Læsaa 1994- (2023)
This thesis focuses on ’Jól’ (yule, Christmas) in ‘Islendinga sogur’ (sagas of Icelanders). To derive the saga's description of jól, all mentions have been counted and examined. Herby three main uses have been discovered. First the use of jól as a fixed point in time. Here, jól is used to describe the yearly cycles or to explain where in the calendar actions took place. This follows a discussion of the different calendar systems in the pre-Christian North. Secondly, the mentions where the word jól are describing yule celebrations, e.g. inviting guests or traveling to yule banquets, drinking, gift-giving, decorations, and plays. In this part, a lot of the text pieces are examined closely to evaluate how the descriptions are related to the society of Iceland or linguistic to the story or plot in the saga. The final part is about the supernatural element which has been the focus of many scholarly works working with Yule. Traditionally ‘draugar’ (ghosts) have been included in the yule understanding, but here ‘berserkir’ (berserks) and ‘jötnar’ (giants, trolls) have been included as well. Besides the standard source-critically account from the traditional historian, there have been used simple statistics to organize the elements and investigate whether previous scholarly works have included a representative number of sources to describe yule. The thesis concludes that yule was an important celebration as everybody knew when it was celebrated and therefore an easy fix point in the calendar. The celebration consisted of drinking parties which worked as statements of alliances. The festivities have most likely included sports games and some religious activities. Supernatural elements are described around Yule in some of the saga. However, ‘bersærks’ and ‘jotun’ seem more related to locations, and ‘draugr’ to darkness, rather than to yule. Furthermore, all the instances of ‘draugr’ are written as educational stories to strengthen the morality of the Christian belief, rather than being an actual part of yule. Ritgerðin ...